Campusübergreifende Lehrforschung im Bachelor- und Master-Modul "Marktforschung und -analyse" zum Thema E-Mobilität: Darstellung der unterschiedlichen didaktischen Vorgehensweisen und der Ergebnisse der Studierenden - Gabriele Schuster; Caterina Fox; Marion Kalteis; Jürgen Kumbartzki; Christian Lucas; Uta Scheunert; Sabine Wießner (IUBH Internationale Hochschule, 2020)
– Competency-oriented teaching has become an important goal of higher education. Instead of "the sage on the stage", edu-cators are encouraged to become a "guide by their side". They should enable students to apply knowledge rather than simply regurgitating it. This paper represents a contribution to this trend and showcases a cooperative teaching project on IUBH six campuses (Düsseldorf, Erfurt, Hamburg, Mannheim, Frankfurt, Nürn-berg). Electromobility was selected as the overall topic of interest for nine marketing research courses scheduled for the 19/20 winter semester. As these courses coincided with the development of the "IUBH Mobility-Kompass", students were able to conduct preliminary research for this instrument. Eight instructors coordinated over 100 bachelor and master students of the marketing management program and coached them in the development of independ-ent research projects. The instructors shared lecture materials and best practices, but organized their teaching and student projects individually, resulting in a wide range of approaches and results. This paper provides an overview of each ap-proach, a critical reflection and a summary of relevant student project outcomes. Overall feedback was very pos-itive from both students and professors and thus this project contributes to the continuous improvement of teach-ing at IUBH.
Keywords: A29; A1; 650; Lehrforschung; Hochschuldidaktik; Interaktive Lehrformen; Marktforschung; Marketing Elektromobilität (E-Mobilität)